2018
DOI: 10.1111/jai.13846
|View full text |Cite
|
Sign up to set email alerts
|

Length–weight relationships for estuarine fishes in South Brazil

Abstract: Summary The present study reports the length‐weight relationships (LWRs) for 18 estuarine species sampled in Guaratuba Bay, South Brazil. For the majority of these 18 species the LWRs are known from the literature, but these estimates do not consider sexes separately which is done in this contribution. Different fishing gears were used in the samplings (cylindrical nets – 1 mm mesh size, bottom trawls – 250 mm mesh size in the arms and 12 mm mesh size in the bag, beach seine – 5 mm mesh size and hook and line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Moreover, the sexual differences may have resulted in these discrepancies of b (general x separated sexes) when we grouped the individuals and compared them to the separated sexes, since their growth types are different. Concerning the fat snook, we presented the LWR for juveniles, while FishBase and other studies in near areas showed this relationship for adults (Froese & Pauly, 2019;Possamai et al, 2019). The juveniles here showed an allometric negative growth, which demonstrates the species is investing more in length than in weight.…”
Section: Discussionmentioning
confidence: 46%
See 3 more Smart Citations
“…Moreover, the sexual differences may have resulted in these discrepancies of b (general x separated sexes) when we grouped the individuals and compared them to the separated sexes, since their growth types are different. Concerning the fat snook, we presented the LWR for juveniles, while FishBase and other studies in near areas showed this relationship for adults (Froese & Pauly, 2019;Possamai et al, 2019). The juveniles here showed an allometric negative growth, which demonstrates the species is investing more in length than in weight.…”
Section: Discussionmentioning
confidence: 46%
“…The juveniles here showed an allometric negative growth, which demonstrates the species is investing more in length than in weight. This is different from the adults which exhibit allometric positive growth (Possamai et al, 2019). When the fat snook reaches maturity (about 194 mm) (Chaves & Nogueira, 2018), it starts as a male and then becomes female (protandric hermaphroditism).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…1), which indicates that this group first increased in weight and then in length. It is inferred that this variation in the b value between the groups is due to differences in size and weight ranges for each group at the beginning of the study since the coefficient can change between populations of the same species depending on life cycle stages (Bagenal, 1978;Cibert et al 1999;Sá et al 2000;Possamai et al 2018), as well as to the low consumption of feed in D1 with respect to the high consumption of sardine in D2. Both b values were higher than those found by Leiva et al (2007) for the same species captured in Colombian waters (b = 2.656).…”
Section: Resultsmentioning
confidence: 99%